منهج مقترح لتعليم اللغة العربية لطلبة المدارس الثانوية الخاصة بالخرطوم وفق المنهج البريطاني ‏ - حسين، عازة عبد الرحمن حمزة (Kulliyah of Education, International Islamic University Malaysia, 2018)
This study aims to prepare a proposed curriculum for teaching the Arabic Language ‎to the private secondary school students in Khartoum in Sudan based on the British ‎curriculum. It also aims to identify its impact on the students' attitudes toward ‎learning the Arabic Language. To achieve these objectives, the researcher used an ‎evaluation method prepared and experimented according the Delphi technique or ‎method. The researcher also constructed a scale to measure the students' attitude ‎toward learning the Arabic Language. The scale's psychometric properties reliability ‎and validity were examined. And its stability was calculated using Cronbach's alpha. ‎To ensure its stability, the test was repeated on the same sample by a two-week ‎interval. The result was in the first round (.748) and in the second round (.943) which ‎indicates the reliability of the questionnaire. Interviews were used to elicit further ‎information from the Arabic Language teachers who teach the study sample. The ‎study sample comprised (111) male and female students and four teachers selected ‎from four private schools using the purposive sampling procedures. The sample was ‎divided into two groups: the experimental group (64 students) and the control group ‎‎(47 students). To answer the research questions, the researcher used the analytical ‎descriptive and quasi-experimental research designs. The Statistical Package for ‎Social Sciences (SPSS) was used to analyze the collected data including (Means, ‎Standard Deviations, Interquartile Range, Analysis of Covariance and Independent ‎Sample t Test). The thematic approach was used to analyze the interviews. The ‎results showed that there were statistically significant differences in the students' ‎attitude mean scores between the experimental and control groups in favor of the ‎former (p≤ 0.05), and there were also significant differences due to gender in favor of ‎female students, (p≤ 0.05). In addition, there were statistically significant differences ‎in the students' pre and post attitude mean scores in the experimental group in favor ‎of the post attitude scale. In the light of the results, suggestions and recommendation ‎were put forward; and the most important one is to review the classification of the ‎Sudanese students studying in private schools according to the British curriculum.‎